Subclinical atherosclerosis is associated with Epicardial Fat Thickness and hepatic steatosis in the general population - Baragetti, A.; Pisano, G.; Bertelli, C.; Garlaschelli, K.; Grigore, L.; Fracanzani, A.; Fargion, S.; Norata, Giuseppe; Catapano, A. (Elsevier, 2016)
© 2015 The Italian Society of Diabetology, the Italian Society for the Study of Atherosclerosis, the Italian Society of Human Nutrition, and the Department of Clinical Medicine and Surgery, Federico II University. Background and aims: Abdominal obesity and hepatic steatosis are ectopic fat depots associated with Metabolic Syndrome (MetS). Epicardial Fat Thickness (EFT) is a newly discovered one, increasing with obesity, insulin resistance and MetS. Therefore we studied whether different ectopic fat markers, and EFT in particular, are associated with MetS and markers of subclinical cardiovascular disease. Methods and results: 868 subjects from the PLIC Study were included, EFT, aortic calcifications, carotid Intima-Media Thickness (c-IMT) and echocardiographic parameters were determined by ultrasound; extra-cardiac atherosclerotic lesions were defined in presence of plaques at both carotid and aortic levels. Hepatic steatosis degrees were defined according to a scoring system. Abdominal adiposity was determined using Dual X-ray Absorbimetry (DEXA). Independently from age, women showed higher EFT versus men (4.5 (0.20-9.00) mm vs 4.00 (0.10-8.00) mm, p = 0.013); EFT was thicker in post-menopausal women (independently from hormone-replacement therapy). EFT, liver steatosis and abdominal adiposity increased with MetS (p < 0.001). EFT was the only ectopic fat marker associated with cardiac dysfunction (OR = 1.340 [1.088-1.651 95% C.I., p = 0.006); liver steatosis and EFT were associated with extra-cardiac plaques (OR = 2.529 [1.328-4.819] 95% C.I., p < 0.001 and OR = 1.195 [1.008-1.299] 95% C.I., p = 0.042; respectively). On top of cardiovascular risk factors, only EFT improved the discrimination of subjects with cardiac dysfunction and atherosclerotic plaques. Conclusions: EFT is associated with left ventricular dysfunction and subclinical atherosclerosis. Our data suggest that EFT may represent an additional tool for the stratification of cardiovascular risk.